2014
DOI: 10.1080/00223980.2013.866535
|View full text |Cite
|
Sign up to set email alerts
|

Why Does Interactional Justice Promote Organizational Loyalty, Job Performance, and Prevent Mental Impairment? The Role of Social Support and Social Stressors

Abstract: Using social exchange theory as a conceptual framework, we investigated the relationship between interactional justice and the outcomes organizational loyalty (affective commitment, turnover intentions), perceived job performance (self-rated performance, personal accomplishment), and mental impairment (cognitive irritation, emotional exhaustion) in an online survey of 218 employees working in the field of computer technology. Specifically, we predicted that interactional justice would heighten the quality of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 79 publications
1
31
0
1
Order By: Relevance
“…However, more research is necessary to investigate whether subjective factors such as social stressors remain important beyond (other) objective factors in predicting job insecurity on a daily level. Our findings about the role of co‐worker conflicts on a daily level of job insecurity are in line with prior research about the consequences that social stressors at work exert on employees’ mental and physical health and on their job attitudes (e.g., Bruk‐Lee & Spector, ; Chen & Spector, ; Dormann & Zapf, ; Harris, Harvey, & Kacmar, ; Hershcovis & Barling, ; Kessler et al, ; Kottwitz, Gerhardt, Pereira, Iseli, & Elfering, ; Meier, Semmer, & Spector, ; Otto & Mamatoglu, ; Pereira et al, ; Spector & Jex, ). Thus, in addition to previous results, the present study shows that job insecurity is yet another negative consequence of social stressors—or, more specifically, conflicts with co‐workers—in the workplace.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…However, more research is necessary to investigate whether subjective factors such as social stressors remain important beyond (other) objective factors in predicting job insecurity on a daily level. Our findings about the role of co‐worker conflicts on a daily level of job insecurity are in line with prior research about the consequences that social stressors at work exert on employees’ mental and physical health and on their job attitudes (e.g., Bruk‐Lee & Spector, ; Chen & Spector, ; Dormann & Zapf, ; Harris, Harvey, & Kacmar, ; Hershcovis & Barling, ; Kessler et al, ; Kottwitz, Gerhardt, Pereira, Iseli, & Elfering, ; Meier, Semmer, & Spector, ; Otto & Mamatoglu, ; Pereira et al, ; Spector & Jex, ). Thus, in addition to previous results, the present study shows that job insecurity is yet another negative consequence of social stressors—or, more specifically, conflicts with co‐workers—in the workplace.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, studies also show that conflicts at work can affect organisations and personal health or well‐being (e.g., Bruk Lee & Spector, ; Dormann & Zapf, ; Hershcovis & Barling, ; Meier et al, ; Otto & Mamatoglu, ). Therefore, social stressors should be reduced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ando and Matsuda [9] explored how the perception of interactional justice influenced the employees' role definition and their study showed that the perception of interactional justice could enlarge their role definition and then increased the organizational citizenship behavior of employees. In addition, Otto and Mamatoglu [24] explored the impact effect of interactional justice on the basis of social exchange theory with an investigation on 218 employees from the electronic information industry. The result showed that the perception of interactional justice could increase the organizational commitment of employees and decrease the turnover intention through the employees' perception of social support.…”
Section: The Perception Of Interactional Justice and Individual-levelmentioning
confidence: 99%
“…Therefore, it helps to create good relationships and enhance the interaction and integration of employees and managers from both merging entities (Ellis et al, 2009). By fostering interaction and through demonstrating respect, studies generally conclude that employees will perceive a high level of organisational fairness, and become more loyal towards the organisation (Otto & Mamatoglu, 2014). Similarly to what other scholars have done (Klendauer & Deller, 2009;Luo, 2007), we combine interpersonal and informational justices, referring to it as interactional justice.…”
Section: Background Literature and Hypotheses Development Imentioning
confidence: 99%